Basic Fibroblast Growth Factor-Anchored Multilayered Mesenchymal Cell Sheets Accelerate Periosteal Bone Formation. (6th July 2017) - Uchida, Kentaro; Inoue, Gen; Matsushita, Osamu; Horikawa, Kyosuke; Sekiguchi, Hiroyuki; Saito, Wataru; Takano, Shotaro; Fujimaki, Hisako; Miyagi, Masayuki; Takaso, Masashi
Abstract : Cell-based regenerative therapy has the potential to repair bone injuries or large defects that are recalcitrant to conventional treatment methods, including drugs and surgery. Here, we developed a multilayered cell-based bone formation system using cells coated with fibronectin-gelatin (FN-G) nanofilms. The multilayered mesenchymal cells (MLMCs) were formed after two days of culture and were shown to express higher levels of BMP-2 and VEGF compared to monolayer cultures of MCs. The MLMCs were used as a graft material in combination with a fusion protein consisting of basic fibroblast growth factor (bFGF), polycystic kidney disease (PKD) domain, and the collagen-binding domain (CBD) of Clostridium histolyticum collagenase. In femur sites grafted with the MLMCs, significantly higher levels of callus volume and bone mineral content were observed compared to the sham controls. The callus volume and bone mineral content were further increased in femur sites grafted with bFGF-PKD-CBD/MLMCs. Taken together, these results suggest that bFGF-PKD-CBD/MLMCs, which can be simply and rapidly generated in vitro, have the potential to promote bone repair when grafted into large defect sites.